Method for manufacturing organic thermoelectric composite materials based on spin coating process
Patent Information
- Application Number
- KR1020250213600
- Authority / Receiving Office
- KR · KR
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2025-12-30
- Publication Date
- 2026-09-02
- Estimated Expiration
- 2045-12-30
Smart Images

Figure 112025148637550-PAT00003_ABST
Abstract
Description
Technology Field
[0001] The present invention relates to a method for manufacturing an organic thermoelectric composite material based on a spin coating process, and more specifically, to a method for manufacturing an organic thermoelectric composite material based on a spin coating process that can improve thermoelectric performance through the combination of a spin coating-based multilayer thin film stacking process and an eco-friendly dual reduction process. Background Technology
[0002] Interest in sustainable energy harvesting technologies is rapidly increasing due to the deepening global energy crisis and environmental issues. Among these technologies, thermoelectric (TE) materials are attracting attention as a promising alternative capable of directly converting waste heat into useful electrical energy. The performance of thermoelectric materials is generally represented by the dimensionless performance index ZT; accordingly, achieving high ZT values requires sophisticated optimization that considers the interdependence between factors of electrical conductivity, Seebeck coefficient, and thermal conductivity, but this poses a practical technical challenge.
[0003] Recent advancements in nanostructured thermoelectric materials and hybrid composites are demonstrating the potential to recover energy from industrial processes, automotive systems, and even human body heat. Inorganic thermoelectric materials such as bismuth telluride, lead telluride, and tin selenide exhibit excellent thermoelectric performance due to their high Seebeck coefficient and low thermal conductivity. However, these materials face limitations in large-area fabrication and their application in wearable and flexible electronic devices due to factors such as raw material scarcity, high manufacturing costs, and low mechanical flexibility.
[0004] In contrast, organic thermoelectric materials utilizing conductive polymers and carbon-based nanomaterials such as graphene or carbon nanotubes possess unique advantages, including lightweight properties, excellent mechanical flexibility, low toxicity, and ease of large-area processing. In particular, the synergistic combination of conductive polymers and carbon nanomaterials is attracting attention as a composite material for next-generation thermoelectric devices, as it can increase electrical conductivity while maintaining low thermal conductivity.
[0005] Graphene oxide (GO) is a chemically oxidized form of graphene that is attracting attention in thermoelectric research due to its large specific surface area, high electrical conductivity, and ease of functionalization. However, the abundant oxygen-containing functional groups (hydroxyl, epoxy, carbonyl, carboxyl, etc.) within the structure of GO are sp 2 It disrupts the carbon network structure, significantly reducing conductivity compared to graphene. This low intrinsic conductivity and the difficulty in controlling the degree of reduction act as major factors limiting thermoelectric performance when using single GO. Therefore, improving the conductivity of GO is recognized as a critical challenge in various electronic device applications. Conventional reduction processes have raised safety and environmental concerns due to the use of toxic reducing agents such as hydrazine or NaOH. In contrast, green reduction processes utilizing eco-friendly reducing agents such as L-ascorbic acid (L-AA) or low-temperature heat treatment are attracting attention as safer and more sustainable alternatives. In particular, thermal reduction processes have the advantage of effectively removing oxygen functional groups while maintaining the carbon framework, and enable the simple, large-area fabrication of single-layer or few-layer graphene.
[0006] Meanwhile, in the field of thin film manufacturing, the Layer-by-Layer (LbL) assembly method is widely utilized as a flexible technology capable of designing and realizing multifunctional thin films. Traditionally, the dipping method has been used for uniform deposition, but recently, the spin coating method has garnered attention for its superior process efficiency, mass production, and material utilization. Unlike the dipping method, spin coating allows for the rapid deposition of each layer within seconds, thereby shortening process time and reducing the risk of contamination. Furthermore, it aligns with sustainable manufacturing processes due to low solution consumption, and allows for precise control of film thickness and uniformity through the control of parameters such as rotation speed, time, and solution concentration. This process control capability is advantageous for adjusting mechanical, optical, and thermal properties, and improves the mechanical stability of the film by strengthening interlayer adhesion through centrifugal force. Therefore, spin coating-based LbL deposition technology is considered a highly promising thin film manufacturing method for applications requiring uniformity, productivity, and cost efficiency simultaneously.
[0007] For this reason, there is a need to develop technology that can effectively improve the electrical and thermoelectric properties of organic thermoelectric composite materials by combining a spin-coating-based multilayer thin film stacking process with an eco-friendly dual reduction process. Prior art literature
[0008] Korean Registered Patent Publication KR 10-1801787 The problem to be solved
[0009] The present invention aims to solve the problems of the aforementioned conventional technology by improving the thermoelectric performance of organic thermoelectric composite materials through the combination of a spin-coating-based multilayer thin film stacking process and an eco-friendly dual reduction process.
[0010] In addition, the present invention aims to solve the problems of the aforementioned conventional technology by improving the conductivity, mechanical stability, flexibility, and eco-friendliness of organic thermoelectric composite materials through the formation of a hierarchical nanostructure. means of solving the problem
[0011] To achieve the above-mentioned technical problem, the present invention discloses a method for manufacturing an organic thermoelectric composite material based on a spin coating process, comprising the steps of: forming a cationic conductive polymer layer by coating a cationic conductive polymer solution on a substrate; and forming an anionic carbon layer by coating an anionic carbon composite solution containing carbon nanotubes and graphene oxide on the cationic conductive polymer layer, wherein the cationic conductive polymer layer and the anionic carbon layer are formed by spin coating.
[0012] Here, the cationic conductive polymer may comprise one or more selected from the group consisting of poly(4-vinylpyridine-costyrene) (PVPS), poly(diallyldimethylammonium chloride) (PDADMAC), polyethyleneimine (PEI), and poly(allylamine hydrochloride) (PAH).
[0013] Here, the carbon nanotube may be included in an amount of 0.015 to 0.05 parts by weight per 100 parts by weight of the anionic carbon composite solution.
[0014] Here, the spin coating can be performed at 2500 to 4500 rpm for 15 to 25 seconds.
[0015] Here, the manufacturing method may further include the step of immersing the composite material in a first heat-treated reducing agent solution; and the step of second heat-treating the immersed composite material.
[0016] Here, the reducing agent solution may include one or more selected from the group consisting of sodium citrate, ascorbic acid, citric acid, glucose acid, and tannic acid.
[0017] Here, the temperature of the first heat-treated reducing agent solution may be 65 to 95 ℃.
[0018] Here, the second heat treatment can be performed at 160 to 190 ℃ for 75 to 105 minutes.
[0019] Here, the cationic conductive polymer layer and the anionic carbon layer can be stacked in sequence at least once. Effects of the invention
[0020] The disclosed technology may have the following effects. However, this does not mean that a specific embodiment must include all of the following effects or only the following effects; therefore, the scope of the rights of the disclosed technology should not be understood as being limited by this.
[0021] According to the present invention, the thermoelectric performance of an organic thermoelectric composite material can be improved through the combination of a spin-coating-based multilayer thin film stacking process and an eco-friendly dual reduction process.
[0022] In addition, according to the present invention, the conductivity, mechanical stability, flexibility, and eco-friendliness of organic thermoelectric composite materials can be improved through the formation of a hierarchical nanostructure. Brief explanation of the drawing
[0023] FIG. 1 is a flowchart illustrating a method for manufacturing an organic thermoelectric composite material according to one embodiment of the present invention. FIG. 2 is a schematic diagram and a schematic diagram illustrating the layer-by-layer assembly process and chemical structure of an organic thermoelectric composite material according to one embodiment of the present invention. Figure 3 is a graph showing the results of a thickness analysis experiment of an organic thermoelectric composite material according to one embodiment of the present invention. Figure 4 is an image showing the results of a surface structure analysis experiment of an organic thermoelectric composite material according to one embodiment of the present invention. FIG. 5 is a graph showing the sheet resistance and electrical conductivity test results of an organic thermoelectric composite material according to one embodiment of the present invention. Figure 6 is a graph showing the experimental results of the Seebeck coefficient and power factor of an organic thermoelectric composite material according to one embodiment of the present invention. FIG. 7 is a graph showing the experimental results of carrier concentration, carrier mobility, output voltage, and output power of an organic thermoelectric composite material according to one embodiment of the present invention. FIG. 8 is a graph showing the XPS and Raman spectrum experimental results of an organic thermoelectric composite material according to one embodiment of the present invention. FIG. 9 is a graph and schematic diagram illustrating the UPS spectrum, elastic modulus, and carrier transport mechanism according to the reduction treatment of an organic thermoelectric composite material according to one embodiment of the present invention. Specific details for implementing the invention
[0024] The present invention is capable of various modifications and may have various embodiments, and specific embodiments are illustrated in the drawings and described in detail in the detailed description. However, this is not intended to limit the invention to specific embodiments, and it should be understood that the invention includes all modifications, equivalents, and substitutions that fall within the spirit and scope of the invention.
[0025] Similar reference numerals are used for similar components when describing each drawing. Terms such as "first," "second," etc., may be used to describe various components, but said components should not be limited by said terms. These terms are used solely for the purpose of distinguishing one component from another.
[0026] For example, without departing from the scope of the present invention, the first component may be named the second component, and similarly, the second component may be named the first component. The term "and / or" includes a combination of a plurality of related described items or any of a plurality of related described items.
[0027] Unless otherwise defined, all terms used herein, including technical or scientific terms, have the same meaning as generally understood by those skilled in the art to which this invention pertains.
[0028] Terms such as those defined in commonly used dictionaries should be interpreted as having meanings consistent with their meanings in the context of the relevant technology, and should not be interpreted in an ideal or overly formal sense unless explicitly defined in this application.
[0029] Throughout this specification, when a part is described as "comprising" a certain component, this means that, unless specifically stated otherwise, it does not exclude other components but may include additional components.
[0030] As used herein, terms of degree such as “about,” “substantially,” etc., are used to mean at or near the stated value when inherent manufacturing and material tolerances are presented in the stated meaning, and are used to prevent unscrupulous infringers from unfairly exploiting the disclosure in which precise or absolute values are mentioned to aid in understanding the invention. Furthermore, throughout this specification, “a step of” or “a step of” does not mean “a step for”.
[0031] Throughout this specification, the term “combination thereof” included in the Markush-type expression means one or more mixtures or combinations selected from the group consisting of the components described in the Markush-type expression, and means including one or more selected from the group consisting of said components.
[0033] Method for manufacturing organic thermoelectric composite materials based on spin coating process
[0034] The present specification discloses a method for manufacturing an organic thermoelectric composite material based on a spin coating process, comprising the steps of: forming a cationic conductive polymer layer by coating a cationic conductive polymer solution on a substrate; and forming an anionic carbon layer by coating an anionic carbon composite solution containing carbon nanotubes and graphene oxide on the cationic conductive polymer layer, wherein the cationic conductive polymer layer and the anionic carbon layer are formed by spin coating.
[0035] FIG. 1 is a flowchart illustrating a method for manufacturing an organic thermoelectric composite material according to one embodiment of the present invention.
[0036] Referring to FIG. 1, it can be seen that the method comprises the steps of: forming a cationic conductive polymer layer by coating a cationic conductive polymer solution onto a substrate; and forming an anionic carbon layer by coating an anionic carbon composite solution containing carbon nanotubes and graphene oxide onto the cationic conductive polymer layer.
[0037] The above-mentioned cationic conductive polymer is a polymer that exhibits cationic properties in an aqueous solution and can play a role in enabling layer-by-layer assembly through electrostatic interaction with anionic carbon composite solution. Specifically, the above-mentioned cationic conductive polymer acquires a net positive charge through partial protonation of functional groups such as pyridine groups, which enables reproducible layer growth with controlled thickness and homogeneity through alternating adsorption with negatively charged carbon nanotube-graphene oxide composites.
[0038] The above cationic conductive polymer may include one or more selected from the group consisting of poly(4-vinylpyridine-costyrene) (PVPS), poly(diallyldimethylammonium chloride) (PDADMAC), polyethyleneimine (PEI), and poly(allylamine hydrochloride) (PAH), but is not limited thereto.
[0039] The carbon nanotubes described above form an anionic carbon composite solution together with graphene oxide and can play a key role in improving electrical conductivity by forming a three-dimensional conductive network within a multilayer thin film. The carbon nanotubes act as a bridge connecting the graphene oxide sheets and effectively promote electron conduction pathways throughout the multilayer through the entanglement of the nanotubes.
[0040] The carbon nanotubes mentioned above may specifically be double-walled carbon nanotubes (DWNT), but are not limited thereto; any carbon nanotube capable of forming a stable dispersion with graphene oxide, such as single-walled carbon nanotubes (SWNT) and multi-walled carbon nanotubes (MWNT), can be applied.
[0041] For every 100 parts by weight of the above anionic carbon composite solution, the carbon nanotubes are preferably included in an amount of 0.015 to 0.05 parts by weight, more preferably in an amount of 0.02 to 0.045 parts by weight, and most preferably in an amount of 0.025 to 0.04 parts by weight. For example, if the carbon nanotubes are included in an amount less than 0.015 parts by weight, it may not be sufficient to form a continuous conductive network, and thus a problem may arise in which the electrical conductivity is significantly lowered. Conversely, if they are included in an amount exceeding 0.05 parts by weight, excessive aggregation of the nanotubes may occur, which hinders uniform dispersion and reduces the homogeneity of the film formation.
[0042] The graphene oxide described above exhibits anionic properties due to the deprotonation of carboxylic acid groups present on the surface and edges, and can perform a dual role of stabilizing carbon nanotubes and enabling electrostatic adsorption during the layer-by-layer assembly process. The graphene oxide improves the stability of colloidal dispersions by adsorbing onto the surface of carbon nanotubes and stabilizing them in aqueous solutions, and as it converts into reduced graphene oxide (rGO) after reduction treatment, sp 2 The carbon network can be restored, and electrical conductivity can be substantially improved.
[0043] For every 100 parts by weight of the anionic carbon composite solution, the graphene oxide is preferably included in an amount of 0.05 to 0.2 parts by weight, more preferably in an amount of 0.08 to 0.18 parts by weight, and most preferably in an amount of 0.1 to 0.15 parts by weight. For example, if the graphene oxide is included in an amount less than 0.05 parts by weight, the carbon nanotubes are not sufficiently stabilized, resulting in a decrease in colloidal stability and aggregation of the carbon nanotubes. Conversely, if it is included in an amount exceeding 0.2 parts by weight, electron scattering increases due to excessive oxygen-containing functional groups and charge transport is hindered, which may result in a problem where it is difficult to obtain sufficient electrical conductivity.
[0044] The rotational speed of the spin coating is preferably 2500 to 4500 rpm, more preferably 3000 to 4000 rpm, and most preferably 3200 to 3800 rpm. In addition, the execution time of the spin coating is preferably 15 to 25 seconds, more preferably 17 to 23 seconds, and most preferably 18 to 22 seconds.
[0045] For example, if the spin coating speed is less than 2500 rpm, the diffusion of the solution is insufficient, which leads to a decrease in the uniformity of the film thickness and a reduction in the precision of the layer assembly. Conversely, if it exceeds 4500 rpm, the film may become excessively thin and discontinuous layers may be formed due to excessive centrifugal force. Additionally, if the spin coating execution time is less than 15 seconds, the uniform diffusion and stabilization of the solution are not sufficiently achieved, resulting in the formation of an uneven film. Conversely, if it exceeds 25 seconds, the viscosity of the solution may increase due to excessive drying, which may hinder uniform diffusion.
[0046] The above manufacturing method may further include the step of immersing the composite material in a first heat-treated reducing agent solution; and the step of second heat-treating the immersed composite material. The above-described double reduction treatment is an essential process for converting graphene oxide into reduced graphene oxide (rGO) to restore the sp² carbon network and substantially improve electrical conductivity. Chemical reduction using a reducing agent solution effectively removes oxygen-containing functional groups to restore the π-conjugation network, and subsequent heat treatment further expands the conjugation domains to strengthen the conductive network.
[0047] In the case of chemical reduction using a reducing agent solution corresponding to the first reduction treatment, it is important to immerse the film material, which has been heated by the first heat treatment, in the reducing agent solution. Through this sequence, the first reduction can be achieved.
[0048] The above reducing agent solution may include one or more selected from the group consisting of sodium citrate, ascorbic acid, citric acid, glucose acid, and tannic acid, but is not limited thereto. Any reducing agent that is environmentally friendly, effective for reducing graphene oxide, and operates under mild conditions sufficient to preserve the integrity of a flexible substrate such as a PET substrate may be used as the reducing agent solution.
[0049] The above first heat treatment is a step of heating the reducing agent solution, which serves to promote the chemical reduction reaction when the composite material is subsequently immersed and to ensure that the reducing agent penetrates uniformly throughout the entire multilayer thin film. At this time, through the appropriate temperature of the heated reducing agent solution, oxygen functional groups of graphene oxide are effectively removed during chemical reduction, while the structural stability of the flexible substrate and the integrity of the film can be maintained.
[0050] The temperature of the first heat-treated reducing agent solution is preferably 65 to 95 ℃, more preferably 70 to 90 ℃, and most preferably 75 to 85 ℃. For example, if the temperature of the first heat-treated reducing agent solution is less than 65 ℃, the chemical reduction reaction may not proceed sufficiently, resulting in incomplete removal of oxygen functional groups and insufficient improvement in electrical conductivity; conversely, if it exceeds 95 ℃, the mechanical properties of the film may deteriorate and process efficiency may decrease due to excessive heat treatment.
[0051] The step of immersing the composite material in the first heat-treated reducing agent solution is preferably performed for 25 to 55 minutes, more preferably for 30 to 50 minutes, and most preferably for 35 to 45 minutes. If the immersion time is less than 25 minutes, there is a problem where the reducing agent does not penetrate uniformly throughout the entire multilayer thin film and the reduction reaction proceeds incompletely; conversely, if it exceeds 55 minutes, problems may arise where the physical properties of the film deteriorate and process efficiency decreases due to excessive chemical treatment. The second heat treatment involves applying additional thermal energy after chemical reduction to further promote the deoxygenation of graphene oxide and sp 2 It plays a role in expanding the conjugation domain of the carbon network.
[0052] The present invention enables the additional removal of residual oxygen functional groups through the secondary heat treatment, significantly reduces structural defects and disorders, and achieves carrier mobility, excellent power factor, etc.
[0053] The temperature of the second heat treatment is preferably 160 to 190 ℃, more preferably 165 to 185 ℃, and most preferably 170 to 180 ℃. In addition, the time of the second heat treatment is preferably 75 to 105 minutes, more preferably 80 to 100 minutes, and most preferably 85 to 95 minutes.
[0054] For example, if the temperature of the second heat treatment is less than 160°C, additional deoxygenation of the graphene oxide may not proceed sufficiently, resulting in residual structural defects and incomplete expansion of conjugation domains, which may limit the improvement of electrical conductivity; conversely, if it exceeds 190°C, thermal deformation of the composite material or substrate may occur, or the film structure may be damaged and mechanical properties degraded due to excessive thermal energy. In addition, if the time of the second heat treatment is less than 75 minutes, uniform reduction across the entire multilayer thin film may not occur, and the improvement of thermoelectric performance may be insufficient; conversely, if it exceeds 105 minutes, the process time may increase without additional performance improvement, leading to a decrease in economic efficiency.
[0055] The manufacturing method of the present invention includes a dual reduction process in which a primary chemical reduction treatment using ascorbic acid and a secondary reduction treatment by heat treatment are sequentially performed on a multilayer thin film structure, thereby improving the reduction efficiency of graphene oxide and promoting the formation of a carbon nanotube-based continuous conductive network, which can effectively improve the electrical conductivity and thermoelectric properties of the organic thermoelectric composite material.
[0056] The above cationic conductive polymer layer and the above anionic carbon layer can be stacked in sequence at least once.
[0057] The cationic conductive polymer layer and the anionic carbon layer are preferably stacked in sequence 4 to 10 times, more preferably 6 to 10 times, and most preferably 7 to 9 times. For example, if the number of stacking times is less than 4 times, sufficient accumulation to form a continuous conductive network is not achieved, so the penetration threshold is not reached and the thermoelectric performance may be significantly low. Conversely, if it exceeds 10 times, additional deposition contributes only to increasing the film thickness rather than improving the conductive network after the penetration threshold has already been exceeded, which may result in a decrease in the rate of conductivity improvement and reduced economic efficiency.
[0059] Hereinafter, the claims of this specification will be explained in more detail with reference to the attached drawings and embodiments. However, as the drawings and embodiments presented in this specification may be modified in various ways by a person skilled in the art and may take various forms, the details described in this invention should not be limited to a specific disclosed form, but should be understood to include all equivalents and substitutions included within the spirit and scope of the invention. Furthermore, the attached drawings are presented to help a person skilled in the art understand the invention more accurately and may be depicted in an exaggerated or reduced size compared to the actual size.
[0061] {Examples and Evaluation}
[0062] The present invention is to be explained in more detail through the following examples, but the following examples are for illustrative purposes only and are not intended to limit the scope of the present invention.
[0064] <Example>
[0065] Example 1
[0066] 1) Ingredients
[0067] Double-walled carbon nanotubes (DWNT, XB type, diameter approx. 3 nm, length approx. 1 μm) were purchased from Continental Carbon Nanotechnologies, Inc. (Houston, Texas, USA). Poly(4-vinylpyridine-co-styrene) (PVPS) and L-ascorbic acid (L-AA, molecular weight 176.12 g / mol) were purchased from Sigma-Aldrich (St. Louis, Missouri, USA).
[0068] DWNT was dispersed at a concentration of 0.03 wt% in an aqueous solution of 0.1 wt% graphene oxide (Graphene oxide, GO, CheapTubes, USA). To obtain uniform dispersion of DWNT and GO in water, water bath sonication was first performed for 30 minutes, followed by tip sonication for 40 minutes under 15 W conditions, and then water bath sonication was performed for an additional 30 minutes.
[0069] Afterward, the resulting dispersion was centrifuged at 4000 rpm, and the supernatant was carefully recovered.
[0070] All chemical substances were used as purchased without any separate purification process. Deionized water (DI water, Milli-Q, Billerica, Massachusetts, USA) with a resistivity of 18 MΩ or higher was used for the preparation of all aqueous solutions.
[0071] 2) Substrate
[0072] For the measurement of thermoelectric properties and transmission electron microscopy (TEM) analysis, a polyethylene terephthalate (PET) film (product name ST 505, thickness 179 μm) manufactured by DuPont Teijin and purchased from Tekra Corporation (New Berlin, Wisconsin, USA) was used as a substrate.
[0073] Prior to deposition, the PET substrate was sequentially washed with methanol and deionized water, and then the surface was activated using a corona treatment device (BD-20C Corona Treatment, Electro-Technic Products Inc., Chicago, Illinois, USA). This surface oxidation treatment is intended to improve the adhesion properties of the initial deposited layer.
[0074] For surface characteristic analysis, a single-sided polished silicon wafer (Si wafer, thickness 500 μm, crystal orientation (100)) supplied by University Wafer (South Boston, Massachusetts, USA) was used as the substrate. Before use, the silicon wafer was sequentially cleaned with acetone, methanol, and deionized water, and then plasma treatment was performed for 5 minutes using a plasma cleaner (Harrick Plasma, Ithaca, New York, USA).
[0075] 3) Film deposition
[0076] PVPS / DWNT-GO multilayer thin films were fabricated using a spin-assisted layer-by-layer (LbL) deposition technique. In the process of the present invention, a positively charged PVPS solution and a negatively charged DWNT-GO suspension were alternately deposited on various substrates such as silicon wafers, PET films, and quartz slides.
[0077] Specifically, each substrate was mounted on a spin coater (ACE-200, Dong-A Industrial, South Korea) and driven at a constant rotational speed of 3000 rpm. 150 μL of a positively charged PVPS solution (0.25 wt%) was quantitatively dropped onto the rotating substrate and spread uniformly for 20 seconds to form a uniform polymer electrolyte layer.
[0078] Subsequently, an equal volume of negatively charged DWNT-GO suspension was deposited on the PVPS layer under the same rotational conditions to form a single double-layer structure. This alternating deposition process was repeated until a desired number of PVPS / DWNT-GO double layers were formed, thereby forming a multilayer film with precisely controlled thickness and uniformity, and thus fabricating a PVPS / DWNT-GO multilayer film.
[0079] 4) Double reduction treatment
[0080] To evaluate the effect of a two-step post-treatment reduction process on the deoxygenation of GO, an assembled PVPS / DWNT-GO multilayer thin film was immersed in a 0.2 wt% L-AA solution heated to 80 °C and reacted for 40 minutes. For further reduction, the film was heat-treated in an oven at 175 °C for 90 minutes. Through this double reduction treatment, the multilayer thin film stacked and double-reduction treated organic thermoelectric composite material (PVPS / DWNT-rGO) of the present invention was prepared (hereinafter referred to as "Example 1").
[0082] Comparative Example 1
[0083] An organic thermoelectric composite material (PVPS / rGO) was prepared in the same manner as in Example 1, except that PVPS / GO was used as the film material and double reduction treatment was not performed (hereinafter referred to as "Comparative Example 1").
[0085] Comparative Example 2
[0086] An organic thermoelectric composite material (L-AA treated PVPS / rGO) was prepared in the same manner as in Example 1, except that PVPS / GO was used as the film material and only chemical reduction treatment (using L-AA) was performed alone (hereinafter referred to as "Comparative Example 2").
[0088] Comparative Example 3
[0089] An organic thermoelectric composite material (L-AA treated and low-temperature heat-treated PVPS / rGO) was prepared using PVPS / GO as the film material in the same manner as in Example 1 (hereinafter referred to as "Comparative Example 3").
[0091] Comparative Example 4
[0092] An organic thermoelectric composite material (PVPS / DWNT-GO) was prepared in the same manner as in Example 1, except that double reduction treatment was not performed (hereinafter referred to as "Comparative Example 4").
[0094] Comparative Example 5
[0095] An organic thermoelectric composite material (L-AA treated PVPS / DWNT-GO) was prepared in the same manner as in Example 1, except that only chemical reduction treatment (using L-AA) was performed alone (hereinafter referred to as "Comparative Example 5").
[0097] <Evaluation>
[0098] 1. Evaluation of Multilayer Thin Film Synthesis
[0099] FIG. 2 is a schematic diagram and a schematic diagram illustrating the layer-by-layer assembly process and chemical structure of an organic thermoelectric composite material according to one embodiment of the present invention.
[0100] Specifically, FIG. 2a is a schematic diagram illustrating a layer-by-layer deposition process through a spin coating method, and FIG. 2b is a schematic diagram illustrating the chemical structure of the polymer and carbon-based nanomaterial used in the synthesis of the organic thermoelectric composite material of the present invention.
[0101] Referring to Fig. 2a, the layer-by-layer deposition process of the present invention via a spin coating method can be observed. This method enables the controlled growth of multilayer thin films by sequentially adsorbing oppositely charged materials onto a substrate. The manufacturing method of the present invention performs the layer-by-layer deposition of a PVPS / DWNT-GO bilayer based on the alternating adsorption of a cationic conductive polymer layer, PVPS, and an anionic carbon layer, a DWNT-GO composite. Incorporating DWNT into the GO solution improves the colloidal stability of the dispersion, thereby promoting the formation of a uniform film during each deposition cycle. The electrostatic interaction between the cationic PVPS and the anionic DWNT-GO is the primary driving force governing the sequential adsorption and ensures reproducible layer growth with controlled thickness and homogeneity. The cationic behavior of PVPS in aqueous solution originates from the partial protonation of the pyridine group, which forms pyridinium ions and imparts a pure positive charge. Conversely, the DWNT-GO dispersion exhibits anionic properties due to the deprotonation of carboxylic acid groups on the GO sheets, which adsorb to the DWNT surface and stabilize it in water. This charge complementarity enables electrostatic assembly between PVPS and DWNT-GO. Photographic images of DWNT in the GO solution demonstrate the stability of this colloidal dispersion after sonication and centrifugation, indicating that the presence of GO prevents significant aggregation of DWNT. Furthermore, AFM and SEM images of drop-casting the diluted solution onto a Si wafer revealed a homogeneous distribution of carbon nanotubes within the GO, with minimal aggregation. This suggests that the integration of GO as a stabilizer effectively alleviates the intrinsic van der Waals forces between nanotubes, thereby promoting integration into a multilayer structure.
[0102] Referring to FIG. 2b, the chemical structures of the polymer and carbon-based nanomaterial involved in the assembly process of the organic thermoelectric composite material of the present invention can be identified. Specifically, the chemical structures of PVPS, a cationic conductive polymer; DWNT, a carbon nanotube; and GO, a graphene oxide are illustrated.
[0103] Figure 3 is a graph showing the results of a thickness analysis experiment of an organic thermoelectric composite material according to one embodiment of the present invention.
[0104] Specifically, FIG. 3a is a graph showing the change in thickness according to the number of cycles of Comparative Example 1, Comparative Example 2, and Comparative Example 3 systems, and FIG. 3b is a graph showing the change in thickness according to the number of cycles of Comparative Example 4, Comparative Example 5, and Example 1 systems.
[0105] Referring to Fig. 3a, the change in thickness following reduction treatment of the Comparative Example 1 (PVPS / GO) system can be observed. Comparative Example 1 exhibited a linear increase in thickness with a growth increase of approximately 38 nm per double layer. This linearity indicates consistent integration of each component during each deposition cycle of the layer-by-layer assembly process. Furthermore, the system after chemical reduction using the chemical reducing agent L-ascorbic acid (L-AA) corresponds to Comparative Example 2, and chemical reduction treatment using L-AA caused a film thickness shrinkage of approximately 24.5% in the Comparative Example 1 film. This reduction is due to the removal of oxygen-containing functional groups and resulted in a more compact film structure.
[0106] The system that underwent additional heat treatment after chemical reduction corresponds to Comparative Example 3, and the low-temperature heat treatment induced a slight decrease in film thickness (about 10%), which was due to the additional deoxygenation of GO and resulted in the densification of the film.
[0107] Referring to Fig. 3b, the change in thickness following the reduction treatment of the Comparative Example 4 (PVPS / DWNT-GO) system can be observed. Comparative Example 4 exhibited a linear increase in thickness with a growth increase of approximately 56 nm per double layer. A higher growth rate was observed in the Comparative Example 4 film using DWNT compared to Comparative Example 1. This is likely due to the three-dimensional structure of carbon nanotubes, and these structural characteristics allow for an improvement in layer thickness. The system after chemical reduction using L-AA in Comparative Example 4 corresponds to Comparative Example 5, and chemical reduction using L-AA caused a film thickness shrinkage of approximately 25.3% in the Comparative Example 4 film. Additionally, in Example 1, a system that underwent additional heat treatment after chemical reduction, the film thickness was found to show a slight decrease (approximately 10%). Overall, the results of the thickness growth indicate that the PVPS / DWNT-GO system exhibits a superior growth rate compared to the PVPS / GO system, and the thin film becomes denser with the reduction treatment.
[0109] 2. Evaluation of Multilayer Thin Film Structure
[0110] Figure 4 is an image showing the results of a surface structure analysis experiment of an organic thermoelectric composite material according to one embodiment of the present invention.
[0111] Specifically, FIG. 4a is an AFM image showing the upper surface of the organic thermoelectric composite material (2 BL) of the present invention, FIG. 4b is an SEM image showing the surface structure, and FIG. 4c is a TEM image showing the internal structure.
[0112] Referring to Fig. 4a, an AFM image of the top surface of Example 1 (2 BL) can be seen. The AFM image showed a uniform deposition of a single GO nanoplate and demonstrated that carbon nanotubes were clearly distributed on the surface. In each surface image, the yellow arrow indicates the exfoliated GO sheet on the surface. Upon additional deposition, the nanotubes formed an increasingly dense and entangled network, indicating nanotube aggregation and interconnection with the additional layer.
[0113] Referring to Fig. 4b, an SEM image of the surface structure of Example 1 (2 BL) can be seen. SEM analysis confirmed that individual nanotubes and bundles are well distributed, creating a continuous conductive network across the entire film surface. The inset image in Fig. 4b shows high-resolution SEM images of GO and DWNT within the layered thin film. This interconnected nanotube network effectively connects the GO nanoplates, facilitating electron conduction pathways throughout the multilayer. Additionally, a broadly interconnected nanotube network with high surface coverage was observed even after four deposition cycles. In other words, GO promotes the effective exfoliation and uniform dispersion of DWNT within the multilayer structure, thereby facilitating the formation of a three-dimensional conductive network characterized by nanotube entanglements similar to the polymer structure. The rope-like morphology observed for the DWNT suggests that the PVPS molecules wrap around the nanotube surface rather than forming alternating layers distinctly separated from the carbon nanotubes. After subsequent reduction treatment, the surface morphology of the multilayer films of Comparative Example 5 and Example 1 (PVPS / DWNT-rGO) was maintained largely consistent with the original structure.
[0114] Referring to Fig. 4c, a TEM image of the internal structure of the PVPS / DWNT-GO of Example 1 (2 BL) can be seen. Individual GO nanoplates (average diameter: 1–1.2 μm) coexist with a clearly observable DWNT network beneath them. The distinct contrast between the GO nanoplates and the DWNTs indicates a uniform and dense distribution of nanotubes interconnecting the GO sheets. The inset image in Fig. 4c is a high-resolution TEM image of GO and DWNT within the layered thin film; the DWNTs appear to be randomly entangled, forming a three-dimensional network structure that exhibits effective dispersion facilitated by GO-assisted exfoliation. Upon magnification, it was confirmed that the nanotube diameter increased from the original size of approximately 2 nm to about 3 nm, indicating a polymer surrounding the nanotubes. These interactions and network structure contribute significantly to the improvement of electrical conductivity and directly enhance thermoelectric properties.
[0116] 3. Evaluation of Thermoelectric Properties
[0117] FIG. 5 is a graph showing the sheet resistance and electrical conductivity test results of an organic thermoelectric composite material according to one embodiment of the present invention.
[0118] Specifically, FIG. 5a is a graph showing the change in sheet resistance as a function of the number of deposition cycles of the organic thermoelectric composite material of the present invention, and FIG. 5b is a graph showing the change in electrical conductivity as a function of the number of deposition cycles.
[0119] Referring to FIGS. 5a and 5b, the sheet resistance and electrical conductivity as a function of the number of deposition cycles of the thin films of Comparative Example 4, Comparative Example 5, and Example 1, each layer deposited on a PET substrate, can be observed.
[0120] Electrical characterization was performed by measuring the sheet resistance of the Comparative Example 4 (PVPS / DWNT-GO) multilayer assembled on a PET substrate using a 4-point probe method. The characteristics of the Comparative Example 1 and Comparative Example 2 systems were not plotted due to their low performance (i.e., sheet resistance >1 MΩ / sq). Although both GO and DWNT are frequently referred to as electrically conductive components, it is important to distinguish their individual roles in this study. GO exhibits poor electrical conductivity (σ) due to its high oxygen content; consequently, the Comparative Example 1 film showed a negligible thermoelectric response. Meanwhile, the inherently conductive DWNT lacked sufficient surface charge to be directly assembled using a layer-by-layer method. In the approach of the present invention, electrostatic assembly was achieved only through co-stabilization with negatively charged GO, which enabled uniform dispersion and deposition. Therefore, the Comparative Example 4 film could not be prepared or evaluated separately, and a hybrid (LBL and reduction) DWNT-GO system was essential to achieve stable layer-by-layer assembly and optimized thermoelectric performance.
[0121] Referring to Fig. 5a, the change in sheet resistance as a function of the number of deposition cycles can be observed. The sheet resistance of Comparative Example 4 decreased from approximately 300 kΩ / sq at 4 BL to 65 kΩ / sq at 10 BL. Comparative Example 5, prepared through subsequent chemical reduction using L-ascorbic acid (L-AA), dramatically lowered the sheet resistance to approximately 70 Ω / sq at 10 BL. The thin film of Example 1, which underwent additional heat treatment after chemical reduction, achieved 48 Ω / sq at 10 BL, further reducing the resistance. The inset graph in Fig. 5a shows the sheet resistance of Comparative Example 4. Thus, the gradual decrease in electrical resistance observed as the number of deposited double layers increases indicates a gradual improvement in electrical conductivity within the multilayer thin film assembly.
[0122] Referring to Fig. 5b, the change in electrical conductivity as a function of the number of deposition cycles can be observed. The corresponding electrical conductivity (σ), calculated from the product of the film thickness (see Fig. 3b) and the reciprocal of the sheet resistance, increased with the deposition cycles, with Comparative Example 4, prior to reduction, reaching 0.27 S / cm at 10 BL. Comparative Example 5, prepared through L-AA reduction of Comparative Example 4, significantly improved thermoelectric performance, achieving 368 S / cm at 8 BL. The observed increase in σ following the deposition of additional layers indicates improved formation and densification of conductive pathways that occur as the DWNT-GO network transitions from a two-dimensional structure to a highly interconnected three-dimensional structure. Beyond 8 BL, the rate of conductivity improvement decreased, reaching 335 S / cm at 10 BL, indicating that the multilayer assembly exceeded the penetration threshold. The flattening of electrical conductivity observed beyond 8 BL suggests that the multilayer structure approaches a penetration threshold, where a continuous and interconnected conductive network is effectively established. The saturation trend of this conductivity and the morphological uniformity observed in AFM analysis support this interpretation. Beyond this point, additional deposition contributes more to film thickness than to enhancing the conductive network. In particular, Example 1, prepared through heat treatment at 175°C for 90 minutes, further improved conductivity, achieving a maximum of 556 S / cm at 8 BL. The inset graph in Fig. 5b shows the electrical conductivity of Comparative Example 4. The reduction conditions used were sufficiently stable to preserve film integrity and material stability on a PET substrate (175 μm thickness), confirming that there was no material loss or structural degradation after heat treatment.
[0123] Figure 6 is a graph showing the experimental results of the Seebeck coefficient and power factor of an organic thermoelectric composite material according to one embodiment of the present invention.
[0124] Specifically, FIG. 6a is a graph showing the change in the Seebeck coefficient as a function of the number of deposition cycles of the organic thermoelectric composite material of the present invention, and FIG. 6b is a graph showing the change in the power factor as a function of the number of deposition cycles.
[0125] Referring to FIGS. 6a and 6b, the Seebeck coefficient and power factor as a function of the number of deposition cycles of the thin films of Comparative Example 4, Comparative Example 5, and Example 1 deposited on a PET substrate can be seen.
[0126] Referring to Fig. 6a, the results of evaluating thermoelectric performance by measuring the Seebeck coefficient (S) as a function of the number of layers can be seen. Positive S values confirmed p-type carrier transport. Initially, S gradually increased with additional layers, achieving 80 μV / K at 8 BL for Comparative Example 4, which is an untreated film without reduction. Comparative Example 4 showed a gradual increase in S as additional layers were stacked. For Comparative Example 5 and Example 1, an increase in S was observed after reduction, achieving 95 and 105 μV / K, respectively, and it was confirmed that Example 1 had the highest value.
[0127] Referring to FIG. 6b, the power factor (PF=S) of the organic thermoelectric composite material of the present invention, calculated at room temperature as a function of the layer based on σ and S. 2 Хσ) can be confirmed. The power factor of Comparative Example 4, which was not reduced, showed a value so low that it was difficult to confirm relatively. Overall, the multilayer thin film showed an increase in power factor similar to σ depending on the thickness. Comparative Example 4 of 8 BL showed a very low power factor at room temperature ( 0.18 μW / m·K 2 While having ), Comparative Example 5, prepared through L-AA treatment, 331.8 μW / m·K 2 It showed improved values, and Example 1 (~390 nm thickness) after low-temperature heat treatment and double reduction showed 612.5 μW / m·K at 8 BL. 2Achieved a power factor as high as that.
[0128] In addition, to evaluate the advantages of the spin-coating-based multilayer stacking process, a direct comparison was further performed with a conventional drop-cast film of the same thickness (300 nm) after the same reduction treatment. As a result, the drop-coated film exhibited significantly lower thermoelectric performance compared to the spin-coated multilayer. These results clearly demonstrate that the layer-by-layer process enables more effective nanostructure control, improved interfacial organization, and enhanced charge transport.
[0129] In the layered structure, the precise stacking of polymer and nanocarbon layers enables optimized energy filtering and efficient carrier mobility, leading to excellent thermoelectric performance. In particular, the order of reduction treatment had a significant impact on the resulting thermoelectric performance. When a layered assembled film was first chemically reduced using L-AA and subsequently subjected to heat treatment (Example 1), a significant improvement in thermoelectric properties was observed. Conversely, when a multilayer thin film was examined after initial heat treatment followed by chemical reduction, the degree of improvement in thermoelectric behavior was found to be negligible. This suggests that the heat treatment was sufficient to convert most of the GO sheets into reduced graphene oxide (rGO) by significantly removing oxygen functional groups. Consequently, subsequent chemical reduction using L-AA could not further reduce the already extensively reduced graphene structure, leading to minimal additional improvement. Therefore, the reduction treatment order of the present invention has a significant enhancing effect on the thermoelectric performance of GO-based multilayer thin films, and the thermoelectric efficiency can be optimized through the controlled reduction method of the present invention.
[0131] 4. Evaluation of highly adjustable thermoelectric operating characteristics
[0132] FIG. 7 is a graph showing the experimental results of carrier concentration, carrier mobility, output voltage, and output power of an organic thermoelectric composite material according to one embodiment of the present invention.
[0133] Specifically, FIG. 7a is a graph showing carrier concentration and carrier mobility after chemical reduction treatment alone, FIG. 7b is a graph showing carrier concentration and carrier mobility after subsequent thermal reduction of the chemically reduced film, FIG. 7c is a graph showing output voltage and output power after chemical reduction treatment alone at a temperature difference of 15.5 K, and FIG. 7d is a graph showing output voltage and output power after subsequent thermal reduction of the chemically treated film at a temperature difference of 15.5 K.
[0134] Referring to Fig. 7a, the carrier concentration and carrier mobility of the layered thin film of Comparative Example 5 can be observed. The reported n and μ values represent the average of measurements taken from three independently prepared samples. Based on the relationship σ = neμ (where e is the elementary charge), both the untreated and reduced multilayers showed a slight decrease in n, while μ increased as the number of layers increased from 4 to 8 BLs. The n of L-AA treated Comparative Example 5 increased by approximately 2 to 3 times compared to Comparative Example 4, and μ improved by a double-order factor. This significant increase in mobility contributes to the high thermoelectric performance of the Comparative Example 5 film after L-AA treatment.
[0135] Referring to Fig. 7b, the carrier concentration and carrier mobility of the layered thin films of Example 1 can be observed. In the case of Example 1, which underwent additional heat treatment compared to Comparative Example 5, μ increased further, while n decreased slightly. The μ of the chemically reduced 8 BL Comparative Example 5 film increased 1.66 times compared to 4 BL, whereas n was 3.26 × 10⁻¹⁰ in 4 BL. 20 cm -3 3.17 Х 10 at 8 BL 20 cm -3 It decreased slightly to . In addition, in Example 1, the μ of the 8 BL thin film was 10.62 cm 2 It was expressed as / V·s, which is 6.79 cmcm² measured for the 4 BL multilayer. 2It shows an increase of more than 50% compared to the mobility of / V·s. The observed simultaneous increase in σ and S is mainly attributed to significantly enhanced carrier mobility facilitated by a highly aligned 3D conductive network, which ultimately leads to a notable improvement in power factor.
[0136] Referring to Fig. 7c, the output voltage and output power of Comparative Example 5 can be observed at a temperature difference of 15.5 K. The circles, squares, and triangles represent the 4, 6, and 8 BL spin-coated layer-by-layer assemblies, respectively. In evaluating thermoelectric performance, it is important to maximize both the output voltage and output power, as these factors directly affect the efficiency and practical applicability of the thermoelectric generator. The measurement of power output from thermoelectric materials is basically governed by the relationship P=I×V, where P is the output power, I is the output current, and V is the output voltage. At this time, the multilayer film sample (2×4 cm 2 The thermoelectric output power of ) was evaluated at room temperature. Maximum output power (Pmax) is achieved when the external load (RL) matches the internal resistance (Ri), and Pmax=V 2 oc / 4Ri (Voc ~ open circuit voltage).
[0137] Referring to Fig. 7d, the output voltage and output power of Example 1 can be observed at a temperature difference of 15.5 K. Regarding the thermoelectric properties subjected to an additional thermal reduction step following chemical reduction treatment, the maximum power of 8 BL Example 1 was 4.57 nW at △T = 15.5 K from the current-power curve. This value represents a 1.69-fold improvement compared to the Comparative Example 5 system, which underwent only chemical reduction. In other words, it is clear that dual-step reduction (low-temperature reduction after L-AA treatment) leads to superior thermoelectric performance, which is primarily attributed to the efficient restoration of graphene basal plane conjugation and improved carrier transport within the reduced graphene oxide nanosheets. Consequently, both Comparative Example 5 and Example 1 showed that the thermoelectric power was proportional to the number of deposited layers, with 8 BL Example 1 generally exhibiting the best results. That is, the combined chemical and thermal reduction treatment for the GO-based layered assembly improved σ, resulting in higher output voltage and power output values.
[0138] FIG. 8 is a graph showing the XPS and Raman spectrum experimental results of an organic thermoelectric composite material according to one embodiment of the present invention.
[0139] Specifically, FIG. 8a is a graph showing the XPS spectrum of the organic thermoelectric composite material (8 BL) of the present invention, and FIG. 8b is a graph showing the Raman spectrum.
[0140] Referring to Fig. 8a, XPS analysis confirms the effective removal of oxygen functional groups and the restoration of the conjugated carbon structure in the reduced graphene oxide sheet in Example 1. It was clearly demonstrated that the chemical and thermal reduction processes effectively converted GO to rGO. The Comparative Example 4 film before reduction exhibited a prominent C 1s peak at 286.1 eV, which is characteristic of significant oxygen-containing functional groups and represents primarily numerous CO bonds. In the case of Comparative Example 5, a significant decrease in the intensity of the C 1s peak at 286.1 eV (the main graphite CC peak at 284.2 eV) was observed, indicating the partial removal of these oxygen-containing groups and the restoration of the conjugated hexagonal carbon network. In particular, in the case of Example 1, the intensity of the C 1s peak at 286.1 eV was further reduced, indicating more extensive removal of oxygen functional groups and enhanced recovery of the graphite domains.
[0141] Referring to Fig. 8b, structural changes in the PVPS / DWNT-GO multilayer film during reduction and conjugated sp 2 The results of further analysis regarding the reconstruction of the carbon network can be confirmed. The Raman spectrum exhibited two prominent characteristic peaks. The sp² of carbon atoms is associated with structural defects and disorders in the graphene sheets due to extensive oxidation. 3 D-band (~1342 cm) attributable to vibration -1 sp reflecting ) and aligned graphene domains 2 G band associated with in-plane stretching vibrations of carbon atom pairs (~1589 cm⁻¹) -1 ) is. Before reduction, Comparative Example 4 exhibited a relatively high intensity ratio (ID / IG) of 0.36, indicating significant decay and oxidation-induced disturbances within the graphene layer. In the case of Comparative Example 5, the ID / IG ratio decreased significantly to 0.21, which is due to sp following the removal of oxygen functional groups. 2This indicates successful partial restoration of the domains and a reduction in structural defects. In particular, in the case of Example 1, the ID / IG ratio was further reduced to 0.11, which indicates improved recovery of graphite order and further suppression of structural defects. These Raman spectroscopic analysis results demonstrate that the combination of heat treatment after chemical reduction (L-AA) is highly effective in restoring the conjugated graphene structure and significantly reduces structural defects in the thin film of Example 1.
[0142] In addition, a red shift in the G band was observed in the Raman spectrum after thermal reduction, which is conjugated sp 2 It is related to the structural recovery of the domains. This shift can be attributed to (i) the removal of oxygen functional groups and the restoration of π-conjugation, (ii) the relaxation of oxidative strain and the reduction of defect density, and (iii) strong interfacial interactions between the reduced graphene oxide, DWNT, and PVPS matrix. These phenomena collectively indicate improved graphite order and are consistent with the results of enhanced electrical conductivity in the multilayer film.
[0143] FIG. 9 is a graph and schematic diagram illustrating the UPS spectrum, elastic modulus, and carrier transport mechanism according to the reduction treatment of an organic thermoelectric composite material according to one embodiment of the present invention.
[0144] Specifically, FIG. 9a is a graph showing the UPS spectrum before and after reduction treatment of the organic thermoelectric composite material of the present invention, FIG. 9b is a graph showing the elastic modulus before and after reduction treatment, and FIG. 9c is a schematic diagram showing the carrier transport mechanism.
[0145] Referring to Fig. 9a, the results of analyzing the electronic structure of the organic thermoelectric composite material of the present invention using UPS can be confirmed. According to Mott's formalism, the Seebeck coefficient S has a direct correlation with the density of states (DOS) gradient near the Fermi level Ef. As a result of the UPS analysis, distinct differences in the spectral gradient and work function were observed between the untreated film and the reduced film, indicating that the reduction process substantially modified the electronic structure. Furthermore, in the case of Comparative Example 5, the gradient of the UPS spectrum was found to be significantly increased compared to Comparative Example 4, which was untreated, implying that the density of states around the Fermi level increased. This change suggests an improvement in the Seebeck coefficient. Additionally, the work function measured in Comparative Example 5 showed a value 0.13 eV higher than that of Comparative Example 4, which reflects the upward shift of the HOMO edge and the Fermi level state located lower relative to the vacuum level. Meanwhile, in the case of Example 1, the work function was found to have increased by 0.12 eV compared to Comparative Example 5. This implies that the HOMO was further shifted upward as the conjugation structure expanded. Therefore, it was proven that a process combining chemical reduction and thermal reduction enhances the p-type characteristics of the multilayer nanocomposite and contributes to an increase in the Seebeck coefficient.
[0146] Referring to Fig. 9b, the elastic modulus of the organic thermoelectric composite material of the present invention can be confirmed. The elastic modulus of the film of Comparative Example 5 was measured to be 3.72 GPa, which is approximately 1.46 times higher than the 2.54 GPa measured for the film of Comparative Example 4 in the non-reducing state. In addition, the film of Example 1 showed an improved elastic modulus of up to 4.17 GPa, which demonstrated that a denser nanostructure was formed by combining chemical reduction and thermal reduction, thereby effectively establishing a load transfer network. Furthermore, as a result of performing repetitive bending and torsion tests on the 8 BL film of Example 1 formed on a PET substrate, the increase in electrical resistance was limited to within approximately 10% even after 100 deformations under a radius of 1.5 cm. No visible cracks or delamination were observed during the test process, proving that the multilayer film possesses excellent mechanical flexibility and stable charge transport characteristics simultaneously. This improvement in mechanical properties is due to the DWNTs surrounded by GO sheets being uniformly and directionally aligned throughout the entire multilayer. In addition, as GO is reduced to rGO, sp 2 The carbon network is restored, thereby strengthening π-π interactions and interfacial adhesion between graphene sheets. Furthermore, the reduction of oxygen functional groups improves the load transfer efficiency between the polymer matrix, DWNT, and rGO, and this effect directly contributes to the observed increase in the elastic modulus.
[0147] Referring to Fig. 9c, the carrier transport mechanism of the organic thermoelectric composite material of the present invention proposed based on the above results can be confirmed. The initial GO-based multilayer structure is sp due to a large amount of oxygen functional groups. 2Conjugation collapses, resulting in restricted carrier transport. However, a chemical reduction process using L-ascorbic acid effectively removes oxygen functional groups, restoring the π-conjugation network and reducing the energy barrier at the interface. Subsequently, a heat-assisted reduction process further expands the conjugation domains, forming continuous conduction pathways across the entire multilayer. In particular, the layered interfaces composed of a quasi-one-dimensional polymer, one-dimensional DWNT, and two-dimensional rGO act as selective energy filters, scattering low-energy carriers and preferentially transporting high-energy carriers, thereby effectively enhancing the Seebeck coefficient. This interface-based energy filtering effect, combined with the density of states near the Fermi level confirmed by UPS analysis and enhanced carrier mobility, provides a synergistic effect that simultaneously increases electrical conductivity and the Seebeck coefficient.
[0148] Generally, GO exhibits low Seebeck coefficients in the range of 5–10 μV / K, while rGO shows values in the range of 10–60 μV / K depending on the reduction level. Additionally, DWNT exhibits p-type thermoelectric properties at the level of approximately 30–40 μV / K. The improvement in the Seebeck coefficient observed in Example 1 is not the result of a simple superposition of the properties of individual components, but rather is attributed to synergistic electronic structure control and carrier transport optimization at the multilayer interface. Accordingly, this suggests that a multilayer structure design with precise control of chemical and thermal reduction processes can effectively improve the performance of flexible thermoelectric devices.
[0150] According to the present invention, the thermoelectric performance of an organic thermoelectric composite material can be improved through the combination of a spin-coating-based multilayer thin film stacking process and an eco-friendly dual reduction process.
[0151] In addition, according to the present invention, the conductivity, mechanical stability, flexibility, and eco-friendliness of organic thermoelectric composite materials can be improved through the formation of a hierarchical nanostructure.
[0152] The foregoing description of the present invention is for illustrative purposes only, and those skilled in the art will understand that other specific forms can be easily modified without altering the technical concept or essential features of the present invention. Therefore, the embodiments described above should be understood as illustrative in all respects and not restrictive. For example, each component described as a single unit may be implemented in a distributed manner, and components described as distributed may likewise be implemented in a combined form.
[0153] The scope of the present invention is defined by the claims set forth below rather than by the detailed description above, and all modifications or variations derived from the meaning and scope of the claims and equivalent concepts thereof should be interpreted as being included within the scope of the present invention.
Claims
Claim 1 A method for manufacturing an organic thermoelectric composite material based on a spin coating process, comprising: a step of forming a cationic conductive polymer layer by spin-coating a cationic conductive polymer solution onto a substrate; a step of forming an anionic carbon layer by spin-coating an anionic carbon composite solution containing carbon nanotubes and graphene oxide onto the cationic conductive polymer layer; a step of immersing the substrate, on which the cationic conductive polymer layer and the anionic carbon layer are formed, in a reducing agent solution that has undergone a first heat treatment; and a step of performing a second heat treatment on the immersed substrate. Claim 2 A method for manufacturing an organic thermoelectric composite material based on a spin coating process, wherein the cationic conductive polymer comprises one or more selected from the group consisting of poly(4-vinylpyridine-costirene) (PVPS), poly(diallyldimethylammonium chloride) (PDADMAC), polyethyleneimine (PEI), and poly(allylamine hydrochloride) (PAH). Claim 3 A method for manufacturing an organic thermoelectric composite material based on a spin coating process, wherein, in claim 1, the carbon nanotube is included in an amount of 0.015 to 0.05 parts by weight per 100 parts by weight of the anionic carbon composite solution. Claim 4 A method for manufacturing an organic thermoelectric composite material based on a spin coating process, wherein, in claim 1, the graphene oxide is included in an amount of 0.05 to 0.2 parts by weight per 100 parts by weight of the anionic carbon composite solution. Claim 5 A method for manufacturing an organic thermoelectric composite material based on a spin coating process, wherein, in claim 1, the spin coating is performed at 2500 to 4500 rpm for 15 to 25 seconds. Claim 6 A method for manufacturing an organic thermoelectric composite material based on a spin coating process, wherein the reducing agent solution comprises one or more selected from the group consisting of sodium citrate, ascorbic acid, citric acid, glucose acid, and tannic acid. Claim 7 A method for manufacturing an organic thermoelectric composite material based on a spin coating process, wherein, in claim 1, the temperature of the first heat-treated reducing agent solution is 65 to 95 ℃. Claim 8 A method for manufacturing an organic thermoelectric composite material based on a spin coating process, wherein, in claim 1, the secondary heat treatment is performed at 160 to 190 ℃ for 75 to 105 minutes. Claim 9 A method for manufacturing an organic thermoelectric composite material based on a spin coating process, wherein, in claim 1, the cationic conductive polymer layer and the anionic carbon layer are stacked in sequence at least once. Claim 10 delete
Citation Information
Patent Citations
Manufacturing method of multilayer thin film for organic thermoelectric composite material using spray coating
KR1020240170148A